The Pricing Strategy of Oligopolistic Competition Food Firms with the Asymmetric Information and Scientific Uncertainty - Li Zhao; Changwei Wang; Xiaohui Peng; Bin Liu; David Ahlstrom (Journal of Food Quality)
The arguments for and against genetically modified (GM) food focus on the characteristics of the scientific uncertainty and asymmetric information for the GM food. How do these two factors affect the competition and pricing strategy of food firms that separate GM food and conventional food conforming to consumer’s right to know? We explore the issue of pricing strategies between two firms producing horizontally and vertically differentiated foods in the context of asymmetric information and scientific uncertainty. The theoretical results show that there are two separating perfect Bayesian equilibria in which the prices of the conventional food and GM food are strategic complements and the profits of two types of firms are both increasing in the price of GM food. The numerical example shows that a decrease of the expected potential net damage as the most sensitive parameter leads to an increase of the profits of the two firms. Additionally, an increase in product differentiation helps to increase the two firms’ profits. Finally, the decrease in risk aversion as the second sensitive parameter helps to increase both products’ prices and quantities and both firms’ profits. This paper contributes by combining food safety regulation with market mechanisms and competition.